The Application of Beyond Centers and Circle Time Approach - Mursid, Mursid (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2016)
This research used qualitative descriptive approach which lead into a field research. BCCT learning in RA Ngalian was regarded as an effective data obtained. It was 73 percent stated agree and the other of 27 percent stated very agree. Constitutionally, supporting factor in applying BCCT method appears in some aspects, such as the location, the headmasterâs competence, and teachersâ competence. As for the implementation in RA (PAUD) of Ngalian District, most of 67 percent of respondents stated agree and the other of 18 percent of respondents stated disagree. The role of teacher as inspiration for their students and as center of learning was not applied yet holistically. The data obtained, it was almost 45 percent of respondents stated agree and 10 percent stated very agree. It means the role of teacher as inspiration was not applied. Meanwhile the weaknesses factor of BCCT learning in RA (PAUD) of Ngalian district was the lack of time management in implementing BCCT method. This took effect in the learning process. The obtained data showed 45 percent stated agree and 9 percent stated very agree. It means that the time management was most recommended in order the BCCT learning could run well. Because of seeing the allotted time was limited, it made students were forced to accomplish some steps being passed. So that, the time management was required. Key words: the application of BCCT, the supporting factor, the weaknesses factor.